PERAN KELUARGA DALAM PENDAMPINGAN DAN PEMULIHAN KEPADA ANAK YANG MENJADI KORBAN KEKERASAN SEKSUAL DI KOTA DUMAI - Muhammad Haviz Burahman; Rina Susanti (CV. ADIBA AISHA AMIRA, 2022)
Sexual violence against children is a form of the serious problem that often occurs in Indonesia. In Riau Province, especially in Dumai City, the Dumai Timur District is the highest contributor to sexual violence against children in Dumai City. The aim of this research is to determine the role of families in assisting children who are victims of sexual violence and the role of families in the physical and psychological recovery of children who are victims of sexual violence. The research method used is descriptive qualitative research. The results showed that the process of assisting the family through assistance from reporting cases to the police and the trial, while the family recovery process brought the victim for a medical checkup, consulted a psychologist, took the victim for recreation regularly, did not bring up the incident that happened to the victim, transferred the victim to another school, and family therapy.